Computer-assisted medical image examination as a complementary exam concerning initial clinical studies. - Lopes Nunes, Jose Pedro; Fonseca Almeida, Luísa; Araújo, José Paulo (Spanish Journal of Medical Education, 2026)
Introduction. The evaluation of medical students during the medical course can have different types of examinations, including written and practical exams. Computer-assisted evaluation has been made available by widely available technology. Methods. We devised a computer-assisted online medical image examination to stand as a complementary exam in a Medical School examination concerning initial clinical studies. The exam was in the multiple-choice format, showing for each question a list of 5 diagnoses, one of which to be chosen, attempting at eliciting fast visual pattern recognition. The exam was carried out by using Moodle software. Non on-site exams were controlled with simultaneous face monitoring by using the Zoom software. The exam included physical examination findings, electrocardiograms, chest X-rays and CT scan, as well as neurologic disease findings. Results. The exam was completed by 264 students, out of 273 enrolled students. The average grade was 15.4 (standard deviation of 2.9) /20, with a range of 6.7-20.0. A total of 9 students received a rating under 10/20. Two students experienced technical difficulties and quit the exam, later replaced by a practical clinical additional exam. Conclusions. Computer-assisted evaluation has been made available by widely available technology. We devised a computer-assisted online medical image examination to stand as a complementary exam in a Medical School examination concerning initial clinical studies. This exam deals with a real and relevant problem: the importance of visual diagnostics in Medicine. It aims at stimulating a different way of thinking, when compared to written tests. Given the easy availability of this type of medical image online exam, alternatives using written text to question about medical images are called into question.